Genistein protects dermal fibrosis in bleomycin-induced experimental scleroderma - Koca, Suleyman Serdar; Dagli, Adile Ferda; Yolbas, Servet; Gozel, Nevzat; Isik, Ahmet (Aves, 2015)
Objective: Genistein, a phytoestrogen, has anti-oxidant, anti-inflammatory, and anti-angiogenic properties. The aim of the present study is to evaluate the protective effect of genistein in bleomycin (BLM)-induced dermal fibrosis. Material and Methods: This study involved four groups of Balb/c mice (n=10 per group). Mice in three groups were administered BLM [100 mu g/day in 100 mu L phosphate-buffered saline (PBS)] subcutaneously for 4 weeks; the remaining (control) group received only 100 mu L/day of PBS subcutaneously. PBS or BLM was injected into the shaved upper back. Two of the BLM-treated groups also received genistein (1 or 3 mg/kg/day, subcutaneously, to the dorsal front of neck). At the end of the fourth week, all mice were sacrificed and blood and tissue samples were obtained. Results: The BLM applications increased the dermal thicknesses, tissue hydroxyproline contents, a-smooth muscle actin-positive cell counts, and led to histopathologically prominent dermal fibrosis. The genistein treatments decreased the tissue hydroxyproline contents and dermal thicknesses, in the BLM-injected mice. Conclusion: Genistein has antifibrotic potential in BLM-induced dermal fibrosis model. However, its therapeutic potentials on human scleroderma require evaluation in future studies.
Keywords: Scleroderma; dermal fibrosis; genistein